Mast cells infiltrate the esophageal smooth muscle in patients with eosinophilic esophagitis, express TGF- beta 1, and increase esophageal smooth muscle contraction - Aceves, Seema S; Chen, Diana; Newbury, Robert O; Dohil, Ranjan; Bastian, John F; Broide, David H (Journal of allergy and clinical immunology, 2010)
Background: Increased numbers of mast cells are present in the esophageal epithelium in patients with eosinophilic esophagitis (EE). However, mast cell infiltration into the esophageal lamina propria (LP) and smooth muscle (SM) and the effects of their products on SM function has not been determined. Objective: We investigated mast cell localization and characterization in esophageal SM, the functional significance of mast cell TGF- beta 1 expression to contraction of human esophageal smooth muscle (HESM) cells in vitro, and the effect of topical corticosteroids on the number of tryptase-positive (MC sub(T)) and chymase-positive (MC sub(C)) mast cells in patients with EE. Methods: MC sub(T)- and MC sub(C)-positive mast cell numbers were quantitated in the epithelium, the LP before and after topical corticosteroid therapy, and the muscularis mucosa in patients with EE and control subjects by using immunohistology. Double immunofluorescence was used to assess mast cell production of TGF- beta 1. The ability of TGF- beta 1 to influence HESM cell contractility was assessed in vitro. Results: In the SM in patients with EE, significantly increased numbers of MC sub(T)- and TGF- beta 1-positive cells (but only low levels of eosinophils) were detected compared with those seen in control subjects. MC sub(T) expressed TGF- beta 1, which increased the contractility of cultured primary HESM cells in vitro. Topical corticosteroid therapy in patients with EE significantly reduced epithelial MC sub(T) numbers but not LP tryptase-chymase-positive mast cell numbers. Conclusions: MC sub(T) numbers, rather than eosinophil numbers, are increased in the SM in patients with EE, express TGF- beta 1, and increase the contractility of HESM cells in vitro. As such, mast cells localized to SM in patients with EE might modulate esophageal contractility.